Overcoming the response instability of MoS2 humidity sensors by hydrochloric acid surface treatment - Maria Kainourgiaki; Menelaos Tsigkourakos; Evangelos Skotadis; Evangelos Aslanidis; Dimitris Tsoukalas (Micro and Nano Engineering, 2023)
The synthesis of MoS2 with chemical vapor deposition (CVD) using sodium molybdate (Na2MoO4) as the Mo precursor produces a big number of large flakes (∼100-300 μm) compared to other CVD methods that use different precursors. In this work, humidity sensors based on MoS2 are developed, whereby MoS2 is grown using this Mo precursor in an aqueous solution form. The final devices exhibit a response-switching during operation under high (>50%) relative humidity conditions, due to the presence of Na2MoO4 residues on their surface. By decreasing the concentration of the aqueous Mo precursor during the CVD process we partially diminish the switching effect, as the Na2MoO4 residue is reduced To completely overcome this issue, we present a post-fabrication surface treatment using hydrochloric acid that removes the Na2MoO4 residue from the devices' surface. Rinsing the devices with an HCl solution results in the elimination of the response-switching effect and the sensors demonstrate a constant positive response from the initial operation steps.